+0  
 
0
168
1
avatar

when dividing by x-1 x+2 x-2 x-3 the polynomial p(x)=x^4+ax^3+bx^2+c+d remainder 0

Guest Jul 25, 2017
Sort: 

1+0 Answers

 #1
avatar+8828 
+1

Do you mean p(x)=x^4+ax^3+bx^2+cx+d ???

 

(x-1)*( x+2)*( x-2)*( x-3)=x4-4x3-1x2+16x-12

 

a=-4  b=-1   c=16   d=-12

 

laugh

Omi67  Jul 25, 2017

19 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details